Generation of Isolated Attosecond Pulses with 20 to 28 Femtosecond Lasers - Feng, Ximao; Gilbertson, Steve; Mashiko, Hiroki; Wang, He; Khan, Sabih D.; Chini, Michael; Wu, Yi; Zhao, Kun; Chang, Zenghu (My University, 2009)
Isolated attosecond pulses are powerful tools for exploring electron dynamics in matter. So far, such extreme ultraviolet pulses have only been generated using high power, few-cycle lasers, which are very difficult to construct and operate. We propose and demonstrate a technique called generalized double optical gating for generating isolated attosecond pulses with 20 fs lasers from a hollow-core fiber and 28 fs lasers directly from an amplifier. These pulses, generated from argon gas, are measured to be 260 and 148 as by reconstructing the streaked photoelectron spectrograms. This scheme, with a relaxed requirement on laser pulse duration, makes attophysics more accessible to many laboratories that are capable of producing such multicycle laser pulses.